Pengembangan Persona Berbasis Survey Menggunakan Analisis Klaster Untuk Representasi Calon Tenaga Kerja - Enjelina Tampubolon; Dedy Kurniawan; Pacu Putra; Rudi Sanjaya (STMIK Budi Darma, 2023)
The phenomenon of difficulty finding work is one of the issues faced by the current generation, especially among young graduates. The Central Statistics Agency (BPS) released data regarding the number of unemployed in Indonesia in 2023, which reached 5.45%. This means that currently there are around seven million people who do not have permanent work. This condition is caused by a lack of readiness of prospective applicants in terms of skills, knowledge and information as well as high job competition. In this research, a survey was conducted on 200 respondents based on random sampling of active students and fresh graduates from various educational backgrounds. The survey data is used in developing personas to represent potential users using cluster analysis. Personas are a user-centered design approach in HCI that helps developers understand their motivations, needs, skills, and challenges. This approach is used when developers have limited knowledge about the individual behavior of target users. Thus, personas can be used to create basic user groups that represent broader needs and characteristics. Persona development also has the advantages of low development costs and fast and easy access. The final results of this research will present the development of two data-based personas from a total of eight clusters formed. Cluster one (n = 24) and cluster two (n = 84) were chosen as the author's guiding data in creating the main persona. The personas presented can be used in research and application development to increase awareness of end-user needs and demands